Online webinars: the new education techniques and methodology, facilitating learning biological chemistry - Aleksandrova, K. V.; Vasylyev, D. A.; Александрова, Катерина Вячеславівна; Васильєв, Денис Андрійович (ТДМУ, 2016)
This article provides a conceptualization of the webinar as a training strategy between lecturer and students using tools or technological resources available in the network. In addition, it describes it and analyzes the experience of organizing a webinar at Zaporizhzhya State Medical University as part of the training course of biological chemistry. We offer results of the review obtained through an online survey and showed the high potential of online training. Key words: webinar, online, training, biological, chemistry. В статті наведено приклад застосування вебінарів, як однієї з форм поліпшення комунікації між викладачем і студентами в стратегії вивчення дисципліни «Біологічна хімія». Наводиться досвід організації вебінарів на кафедрі біологічної хімії в Запорізькому державному медичному університеті. Отримані результати показали високий потенціал онлайн-навчання